Effects of two intermittent fasting strategies on postprandial lipid metabolism in adults - SHAO Manman; WEI Xiaohui; LI Yuanchao; XU Mingjing; YING Tao; HE Gengsheng; LIU Yuwei (Shanghai yufang yixue)
ObjectiveTo investigate the effects and potential mechanisms of morning and evening fasting on postprandial lipid responses, a post hoc analysis based on a crossover randomized controlled trial was conducted to assess the effects of different fasting strategies on postprandial lipid metabolism in community residents in Shanghai.MethodsA total of 23 participants took part in a randomized crossover trial involving two intervention days: morning fasting and evening fasting, with a washout period of 6 days between intervention days. Two-way analysis of variance was used to test the differences in total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and the relative expression of circadian clock genes before and after the next meal under fasting. Wilcoxon rank sum tests were used to analyze the different metabolites between the two groups. Principal component analysis and Orthogonal partial least squares-discriminant analysis were conducted to evaluate the ability of metabolites to differentiate between morning fasting and evening fasting and identify the important differential metabolites. After adjusting for age, sex, and BMI, a partial correlation analysis was performed to identify metabolites associated with plasma lipids. In addition, important metabolites associated with plasma lipids were computed by pathway enrichment analysis.ResultsAfter evening fasting intervention, fasting TG level [(0.37±0.29) vs (0.27±0.18)] mmol·L-1, fasting and postprandial change values in TC [(2.74±0.47) vs (2.51±0.27)] mmol·L-1 and LDL-C [(1.32±0.38) vs (0.99±0.27)] mmol·L-1 were significantly lower than those after morning fasting (P<0.05). While, change values of fasting LDL-C [(0.89±0.37) vs (1.14±0.37)] mmol·L-1 and TG [(1.14±0.19) vs (1.28±0.17)] mmol·L-1 were significantly higher than those after morning fasting intervention (P<0.05). After fasting intervention, the relative expression of AMPK, CRY1, CLOCK, MTNR1B, AANAT, and ASMT was correlated with the amount of plasma lipid changes (P<0.05). Specifically, CLOCK and AANAT were upregulated following evening fasting and downregulated after morning fasting. Among the 217 important differential metabolites, 111 were correlated with plasma lipids, and which were primarily enriched in the cysteine and methionine metabolism pathways (P<0.05).ConclusionCompared to morning fasting, evening fasting was more effective in improving postprandial lipid responses, indicating that an evening fasting window during intermittent fasting could be conducive to cardiovascular disease prevention in adults. Meanwhile, it is suggested that morning and evening fasting may affect lipid responses through circadian rhythm oscillations and the cysteine and methionine metabolism pathways.